Introductory physical science - Haber-Schaim, Uri (Englewood Cliffs, New Jersey : Prentice-Hall, 1987)
The basic purpose of the course has not changed. The program seeks to give all students a beginning knowledge of physical science and to offer insight into the means by which scientific knowledge is acquired.
1. Introduction -- 2. Volume and mass -- 3. Characteristics properties -- 4. Solubility -- 5. The separation of substances -- 6. Compounds -- 7. Elements -- 8. The atomic model of matter.
Includes index.
Keywords: PHYSICS -- STUDY AND TEACHING (SECONDARY)